CuO Nanostructures Based Electrochemical Sensor for Simultaneous Determination of Hydroquinone and Ascorbic Acid - Buledi, Jamil A.; Ameen, Sidra; Khand, Nadir H.; Solangi, Amber R.; Taqvi, Iqleem H.; Agheem, Muhammad H.; Wajdan, Zahid (Electroanalysis (New York, N.Y.), 2020)
A simple, sensitive and reliable electrochemical sensor has been developed based on CuO nanostructures modified glassy carbon electrode for simultaneous determination of hydroquinone (HQ) and ascorbic acid (AA). The CuO nano material was synthesized by aqueous chemical growth method using different sources of OH. The characterization of nano material was performed by Fourier transform infrared spectroscopy, X‐ray diffraction, field emission scanning electron microscopy and energy dispersive X‐ray spectroscopy. The glassy carbon electrode was modified by CuO nano material using drop cast method and studied by cyclic voltammetry. The CuO/GCE exhibited excellent electrocatalytic activity towards the oxidations of HQ and AA in borate buffer solution (pH 8.0) and the corresponding electrochemical signals have appeared as two well resolved oxidation peaks with significant peak potential differences of (0.21V vs. Ag/AgCl). Differential pulse voltammetry was used for simultaneous determination of HQ and AA using the CuO/GCE. At the optimum conditions, for simultaneous determination by synchronous change of the analyte concentrations, the linear response ranges were between 0.0003–0.355 mM for HQ and 0.0001–0.30 mM for AA respectively. Furthermore, CuO/GCE was successfully applied for the independent determination of AA in fruit juices as well as for the simultaneous determination of HQ and AA in cosmetic samples.